Reconciling global mean and regional sea level change in projections and observations - Jinping Wang (Nature Portfolio, 2021)
Evaluating sea-level projections used by the IPCC is challenging due to the short overlap with measurements. Here, the authors show that observed global and regional sea-level trends confirm projections and that the acceleration of sea-level rise is between the one expected from the scenarios RCP4.5 and RCP8.5.